Sueños y visiones iniciáticas en las vidas de los santos estilitas - Narro, Ángel, 1985- (2019)
The lives of the Stylite saints share many common literary motifs structuring the story of each text. At the same time, these motifs clearly show how the biographies of these saints were connected among themselves and even may reveal the existence of a specific hagiographical genre. Among them, the presence of dreams and visions are of great importance. Thus, an overview of the scenes in which these elements are featured is absolutely necessary to establish intertextual or generic relationships among the lives of these saints of the Middle Byzantine period.
Keywords: Santos; Hagiografía; Biografía